INFORMATION AIMED AT MANIPULATING YOUTH CONSCIOUSNESS AND PROTECTING YOUNG PEOPLE FROM SUCH THREATS AND ATTACKS - Mamatov Tuxtamurod Otamurodovich; Ziyatova Iroda Suyunovna (Innovate Conferences, 2025)
This article scientifically analyzes the priority characteristics of protecting young people from destructive information that rapidly penetrates their consciousness in the current era of globalization. Globalization refers to the process of worldwide economic, political, cultural integration and unification. Its most notable features include the international division of labor, free movement of capital, labor, and production resources, standardization of legislation, economic and technological processes, as well as the merging and convergence of different cultures. As globalization systemically encompasses all spheres of society, protecting youth from any form of informational aggression is of crucial importance.
Keywords: Information, globalization, aggression, social consciousness, ideological processes, information dissemination, internet systems, methods, tools.